DISTRIBUTED ACOUSTIC SENSING (DAS) FOR GEOTHERMAL EXPLORATION: A CASE STUDY OF THE KIZILDERE GEOTHERMAL FIELD - Putra, Ahmad Dedi; Abdul Latiff, Abdul Halim; Mohd Noh, Khairul Arifin; Aparajita, Made Jnanaparama; Pascaloa, M. Rafif; Naufal, Harish Hartsa (Prodi Fisika FST UNJA, 2026)
Geothermal resources have been popular around the world as a cleaner type of alternative energy source to hydrocarbons. Geothermal resources can be used for many purposes such as power generation, direct use, and more. In exploring geothermal resources, details and extensive investigations are required. Distributed acoustic sensing (DAS) is an advanced technology that is becoming more widely used in geoscientific studies, particularly for geothermal exploration. DAS records seismic signals using fiber optic cable instead of geophones, offering advantages over conventional methods in terms of cost, ease of deployment, and capability for continuous real-time monitoring. In this paper, we present a DAS data simulation to study the potential of DAS in geothermal exploration. This study involved several steps, including constructing a geological model based on the Kizildere Geothermal Field Model, simulating seismic data for DAS, and analyzing the DAS data in terms of signal quality and subsurface imaging resolution. The results demonstrated that DAS effectively imaged the subsurface and produced structural images comparable to those from geophones. Although DAS amplitudes are lower, the geological features remain clearly visible, suggesting that DAS is a viable and promising technology for geothermal exploration.